Observation of the high resolution infrared absorption spectrum of CO₂ molecules isolated in solid parahydrogen - Tam, Simon; Fajardo, Mario E. (Физика низких температур, 2000)
We report the observation of high resolution (0.008 cm⁻¹) infrared absorption spectra of CO₂ molecules isolated in solid parahydrogen(pH₂) matrices at T=2.4 to 4.8 K. Several extremely sharp (0.01 to 0.04 cm⁻¹ full-width-at-half-maximum) absorption features appear in the 2343.5 to 2345 cm⁻¹ region. We assign the three strongest peaks to the v3 mode of isolated CO₂ molecules. The spectra are consistent with trapping of the CO₂ molecules in three distinct double-substitutional sites in hcp and fcc regions of the pH₂ solid. We offer several hypotheses as to the origins of the numerous weaker absorption features.